Answer:
Step-by-step explanation:
(x^2+y^2)^2=(x^2)^2+2x^2y^2+(y^2)^2
Adding and substracting 2x^2y^2
We get
(x^2+y^2)^2=(x^2)^2+2x^2y^2+(y^2)^2 +2x^2y^2-2x^2y^2
And we know a^2-2ab+b^2=(a-b)^2
So we identify (x^2)^2 as a^2 ,(y^2)^2 as b^2 and -2x^2y^2 as - 2ab. So we can rewrite (x^2+y^2)^2=(x^2 - y^2)^2 + 2x^2y^2 + 2x^2y^2= (x^2 - y^2)^2+4x^2y^2= (x^2 - y^2)^2+2^2x^2y^2
Moreever we know (a·b·c)^2=a^2·b^2·c^2 than means 2^2x^2y^2=(2x·y)^2
And (x^2+y^2)^2=(x^2 - y^2)^2 + (2x·y)^2
Answer:
-33 and -21
Step-by-step explanation:
-36, <u>-33</u>, -30, -27, -24, <u>-21</u>, -18
-36
-36 + 3 = -33
-33 + 3 = -30
-30 + 3 = -27
-27 + 3 = -24
-24 + 3 = -21
-21 + 3 = -18
Answer:
Levi would have to pay $94 if he bought all 5 kids movie tickets and 6 snacks for everyone to share (god that's a lot of money for a movie)
Step-by-step explanation:
C=7•2=14 this should be right idk